GAMBARAN PENGETAHUAN ANAK TENTANG JENIS MAKANAN KARIOGENIK TERHADAP TERJADINYA KARIES GIGI PADA SISWA/I KELAS V-B SD NEGERI 068003 KAYU MANIS PERUMNAS SIMALINGKAR MEDAN TUNTUNGAN - Sri Junita Nainggolan (Poltekkes Kemenkes Medan, 2019)
Carcinogenic foods can cause tooth decay (dental caries). Carcinogenic food comes in the form of sweetfood like candy, chocolate, cookies, sugar and other food which is starchy, sticky, carbohydrated andcrumbled in the mouth. This research was a descriptive study with survey method aiming to find out thedescription of children’s knowledge about kinds of carcinogenic food towards the occurrence of dentalcaries among grade 5b students at SDN 068003 Kayu Manis Perumnas Simalingkar Medan Tuntungan. Thenumber of the samples was 35 students. The data were collected through the questionnaires and directexamination to the patients’ oral cavity. The result showed that 30 students (85%) had good knowledgeabout the types of cariogenic food and 5 students (15%) had medium knowledge. Through the directexamination to 35 students, 24 students (68%)had caries in milk teeth, 14 students (40%) had caries inpermanent teeth. It is expected that students choose healthy food and reduce consuming sweet foods that canlead to dental caries.